Planar cell polarity genes Frizzled3a, Vangl2, and Scribble are required for spinal commissural axon guidance. Issue 1 (December 2016) - Sun, Simon; Purdy, Ashley; Walsh, Gregory
Abstract Background A fundamental feature of early nervous system development is the guidance of axonal projections to their targets in order to assemble neural circuits that control behavior. Spinal commissural neurons are an attractive model to investigate the multiple guidance cues that control growth cone navigation both pre- and post-midline crossing, as well as along both the dorsal–ventral (D–V) and anterior–posterior (A–P) axes. Accumulating evidence suggests that guidance of spinal commissural axons along the A–P axis is dependent on components of the planar cell polarity (PCP) signaling pathway. In the zebrafish, the earliest born spinal commissural neuron to navigate the midline and turn rostrally is termed commissural primary ascending (CoPA). Unlike mammalian systems, CoPA axons cross the midline as a single axon and allow an analysis of the role of PCP components in anterior pathfinding in single pioneering axons. Results Here, we establish CoPA cells in the zebrafish spinal cord as a model system for investigating the molecular function of planar cell polarity signaling in axon guidance. Using mutant analysis, we show that the functions of Fzd3a and Vangl2 in the anterior turning of commissural axons are evolutionarily conserved in teleosts. We extend our findings to reveal a role for the PCP genescribble in the anterior guidance of CoPA axons. Analysis of single CoPA axons reveals that these commissural axons become responsive to PCP-dependent anterior guidance cues even prior to midline crossing. When midline crossing is prevented bydcc gene knockdown, ipsilateral CoPA axons still extend axons anteriorly in response to A–P guidance cues. We show that this ipsilateral anterior pathfinding that occurs in the absence of midline crossing is dependent on PCP signaling. Conclusion Our results demonstrate that anterior guidance decisions by CoPA axons are dependent on the function of planar cell polarity genes both prior to and after midline crossing.